Design of an Audit Instrument for the Internship Information System (IIS) Based on COBIT 2019 (A Case Study at Universitas XYZ) - Atika Naiylatan Syirfa; Renny Sari Dewi; Rindu Puspita Wibawa (Universitas Negeri Surabaya, 2025)
The Internship Information System (IIS) at XYZ University plays a key role in managing student internship administration but faces challenges such as data access issues, inaccurate information, and delayed updates. The transition to a new system occurred without evaluating IIS performance, risking similar problems in the future. This study aims to design an audit working paper based on COBIT 2019’s Monitor, Evaluate, and Assess (MEA) domain to systematically evaluate IIS performance, control, and compliance aspects. A qualitative case study approach was applied, using interviews, observations, and document analysis at the Directorate of Cooperation, Information Technology, and Data Center. The results indicate weaknesses in performance monitoring, control documentation, and compliance reporting. The proposed audit working paper, consisting of process documents, checklists, and audit steps, is applicable as an internal audit tool. This study concludes that the MEA domain of COBIT 2019 is effective as a foundation for developing audit instruments for information systems in higher education.